Animal Feed Technology and Rural Entrepreneurship - Sharma, Vishnu; Sharma, Sanjita; Karnani, Monika; Kumawat, Manish; Mathur, Manisha (Indian Farming, 2016)
All the given technologies indicate that livestock owners should follow scientific management and feeding practices to improve production. These technologies are helpful to reduce the gap between the urban and rural communities and empower them. For the success of these nonfarm enterprises, there is a need for careful planning, back up support for supply of inputs and marketing. Dedicated voluntary agencies can promote such activities by providing technical training, business planning and linkages with various institutions. Various sources of finance are through Commercial banks, Cooperative banks, Agriculture and Rural development banks, Regional rural banks, Non banking finance companies etc. It is through various technologies and supporting infrastructure that rural employment can be generated for providing livelihood to millions of poor families.